(untitled) (Proceedings of the World Conference on Media and Mass Communication, 2025)
“The new will kill the old”. It is in human nature to be afraid of the new and to try to keep the old. It is also in human nature to embrace the new and to abandon the old. In the business world there is no place for fear. In business, threats are seen as challenges and opportunities. The appearance of the Internet was first considered as a threat to the “old” media, but technology development has opened new opportunities and also set new challenges. New business models have emerged to adapt to the digital reality and strengthen their positions in the market. This paper aims at exploring the prevailing strategies of three leading Bulgarian traditional media and to reveal the key factors for success. Qualitative analyses of observation and quantitative analysis of secondary research data overcome the shortcomings of mediametrics. The principal results stipulate that traditional media have adopted business models that consider the specifics of the industry, the development of digital technology and the expectations of consumers and advertisers. Their success is due to the preservation of their historical advantages as source of information and their ability to adopt the changes. The business models of Bulgarian media are in line with current global trends and reflect the opportunities provided by the development of new technologies and omnipresent digitalization. The most successful are the media, which constantly study their audience and manage to lead the transformation. The paper contributes to the better understanding of the changing media landscape in Bulgaria and the key factors for traditional media in a world dominated by social media.